2020
DOI: 10.1016/j.jeurceramsoc.2020.02.032
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ta doping and irradiation with He+ ions on photoluminescence of MgAl2O4 spinel ceramics

Abstract: Photoluminescence (PL) properties of pristine and Ta-doped MgAl 2 O 4 spinel ceramics prepared via spark plasma sintering technique and irradiated with He + ions were studied. The results indicate strong influence of the grain boundaries on PL spectra. Ta doping promotes the formation of O and Al vacancies at the grain boundaries leading to an increased number density of F + centres. The ionised irradiation forms antisites preferentially at the grain boundaries, which inhibit excitonic PL and exciton energy tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…The cation inversion model introduced in 1932 12 is commonly assumed to be the only type of disorder in the spinel structure, and it is still widely applied. 13,14 Theoretically, the energy of formation for other defects such as interstitials and vacancies is too high to be relevant compared with inversion and as a result they are typically neglected. 15,16 The theoretical study of archetypical spinel MgAl2O4 by Ball et al suggested that the formation energy of interstitials or vacancies is lowered when either is in the vicinity of another point defect of opposite charge.…”
Section: Introductionmentioning
confidence: 99%
“…The cation inversion model introduced in 1932 12 is commonly assumed to be the only type of disorder in the spinel structure, and it is still widely applied. 13,14 Theoretically, the energy of formation for other defects such as interstitials and vacancies is too high to be relevant compared with inversion and as a result they are typically neglected. 15,16 The theoretical study of archetypical spinel MgAl2O4 by Ball et al suggested that the formation energy of interstitials or vacancies is lowered when either is in the vicinity of another point defect of opposite charge.…”
Section: Introductionmentioning
confidence: 99%
“…We observed from PLE spectra that, after the irradiation, the interband transitions (h≥5.05 eV) were stronger attenuated than the excitonic transitions (4.35 eV), which is most probably connected to charged defects, which provoke an effective trapping and non-radiative recombination of the conduction band (CB) electrons and valence band (VB) holes. The strong inhibition of interband transitions is common for spinel materials [31][32][33][34]. In contrast, for non-charged particles, such as excitons, the radiative decay could be much more probable.…”
Section: Resultsmentioning
confidence: 99%
“…TiO 2 formed the TiAl 2 O 5 phase not only in the grain boundary region but also in the grain interior through the reaction with spinel. MgAl 2 O 4 has the characteristics of high melting point, good thermal shock resistance, and good chemical stability, [8][9][10] and is widely used in ceramics, [11][12][13] optics, 14,15 cement, [16][17][18] metallurgy, [19][20][21] and other fields, and its excellent performance meets most requirements of heat storage materials for solar thermal power generation systems. However, the synthesis temperature of MgAl 2 O 4 is higher.…”
Section: Introductionmentioning
confidence: 99%